Application of Geo-informatics for Survey the Ephiphytic Plants in Tad Sung Waterfall Forest Park, Kalasin Province - Prasertsri, Narueset; Sangpradid, Satith; Buasri, Nutchanat; Utta, Theeraya; Chusrithong, Damrongsak; Angkahad, Thinnakon (Journal of Applied Informatics and Technology, 2021)
Application of Geo-informatics for explore the Epiphyte plants in Tat Sung Waterfall Forest Park, Kalasin Province. This research aims to 1) Exploring the diversity total no, and types of this plants 2) Apply the Geo-informatics to present the point and distribution of this plants on the map by exploring in the area of Tat Yao, Tad Sung Waterfall, and a radius of 100 meters from waterfall. The results revealed that 4 types and 13 families namely ferns, orchids, parasites and mosses. The very less common species are ferns, such as Platycerium wallichii Hook., Pyrrosia adnascens (Sw.) Ching., Davallia denticulata (Burm. f.) Mett. ex Kuhn. The total of plants are 345 32 22 clumps respectively. The most common orchids are Dendrobium delacourii Guillaumin., Dendrobium nathanielis Rchb.f. and Dendrobium pulchellum Roxb. Ex Lindl., the total of this plants are 54 34 and 21 clumps respectively. The most common of parasites is Drynaria (Bory) J. Sm., Hoya kerrii Craib (Sweetheart)., and Scindapsus officinalis (Roxb.) Schott. The mosses that is found Bryophyta. Less common orchids include Doritis pulcherrima Var. Buyssoniana., Cirrhopetalum lepidum Zbl. Schltr. Sm. And Aerides multiflora Roxb. All types of this plants are something that helps keep the shade beautiful, helps to purify the air and an index indicating the abundance of this area. The less common species should be deserving to be preserved. Because due to born on low places such as on the trees and rocks. The surrounding area is deciduous and mixed-deciduous forests. Which forest fires often occur in to dry season will be produce some plants that are born in the lowlands may become extinct in the future.